Descriptive Survey Study : Teacher and Student Perception in the Implementation of Deep Learning in Physics Learning - Dasmo Dasmo; Dulhamin Arif; Muhamad Sofiandi; Ani Hoerunisa; Nurzeini Herdiansyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Education in the 21st century demands learning processes that foster deep, meaningful understanding. Within the framework of the Merdeka Curriculum, deep learning is regarded as an essential approach to support students in developing critical thinking, reflective skills, and the ability to connect scientific concepts to real-life contexts. This study aims to describe teachers’ and students’ perceptions of the implementation of deep learning in physics instruction at SMAN 2 Lembang. A descriptive survey design was employed, integrating both qualitative and quantitative data. The data were collected through questionnaires, semi-structured interviews, classroom observations, and instructional documentation. Participants included physics teachers and eleventh-grade students. Data analysis followed the stages of reduction, presentation, and conclusion drawing. The findings reveal that teachers generally possess a solid understanding of deep learning principles, although various challenges persist in its implementation, such as limited instructional time, laboratory constraints, and students’ readiness for reflective and independent learning activities. Most students perceived that deep learning helped them achieve a deeper understanding of physics concepts, even though some still required guidance in exploratory and reflective tasks. Supporting factors included school policies that encourage innovation and teachers’ motivation to improve instructional practices, while inhibiting factors involved uneven learning facilities and differences in student preparedness. Overall, the study indicates that deep learning has the potential to enhance the quality of physics learning. However, its effective implementation requires continuous support through teacher training, improved instructional resources, and adaptive strategies aligned with the school context.